Strategi Pemasaran Digital dan Entrepreneurial Agility sebagai Upaya Meningkatkan Keunggulan Bersaing Pedagang Pasar Sampangan - Mokhamad Arwani (Community : Jurnal Pengabdian Pada Masyarakat, 2026)
The development of digital technology has encouraged traditional market traders to adapt in order to maintain their business competitiveness. One of the traditional markets facing this challenge is Sampangan Market in Semarang, where most traders still rely on conventional marketing methods and have not optimally utilized digital media. This community service program aimed to improve traders’ capabilities in implementing digital marketing strategies and entrepreneurial agility to strengthen their competitive advantage. The implementation methods included observation, socialization, digital marketing training, assistance in the use of business social media, and evaluation of digital marketing practices. The training materials focused on the use of WhatsApp Business, Instagram, and Facebook as promotional tools for business activities. The results showed that traders began to understand the importance of digital marketing, were able to use social media for product promotion, and demonstrated better adaptability to changing market demands. Improved digital competence and entrepreneurial agility helped traders expand market reach and strengthen business competitiveness.